Leveraging Generative AI Tools for Adapting Open Educational Resources OER in Academic Libraries - Dhanya Lijo (20567918) (2025)
Presentation slides of a session presented at the Artificial Intelligence and the Future of Libraries and Librarianship symposium hosted in Qatar in February 2025 by Northwestern University in Qatar in collaboration with the IFLA IT section. The rapid advancement of generative AI technologies presents a transformative opportunity for academic libraries to enhance the accessibility and adaptability of Open Educational Resources (OER). This presentation explores the integration of various generative AI tools to customize and optimize OER, thereby addressing diverse learning needs and promoting inclusive education. Generative AI tools, such as ChatGPT, Copilot and other machine learning models, offer innovative solutions for content creation, modification, and enhancement. These tools can generate text, images, and multimedia content, enabling librarians and educators to tailor OER materials to Other Information Conference information: Artificial Intelligence and the Future of Libraries and Librarianship License: https://creativecommons.org/licenses/by/4.0/ See conference program: https://www.qatar.northwestern.edu/events/library-symposium.html#program-2